Obesity Surgery and Cancer: What Are the Unanswered Questions? - Castagneto-Gissey, Lidia; Casella-Mariolo, James; Casella, Giovanni; Mingrone, Geltrude (Frontiers in Endocrinology, 2020)
Obesity has become a global epidemic with a soaring economic encumbrance due to its related morbidity and mortality. Amongst obesity-related conditions, cancer is indeed the most redoubtable. Bariatric surgery has been proven to be the most effective treatment for obesity and its associated metabolic and cardiovascular disorders. However, the understanding of whether and how bariatric surgery determines a reduction in cancer risk is limited. Obesity-related malignancies primarily include colorectal and hormone-sensitive (endometrium, breast, prostate) cancers. Additionally, esophago-gastric tumors are growing to be recognized as a new category mainly associated with post-bariatric surgery outcomes. In fact, certain types of surgical procedures have been described to induce the development and subsequent progression of pre-cancerous esophageal and gastric lesions. This emerging category is of great concern and further research is required to possibly prevent such risks. Published data has generated conflicting results. In fact, while overall cancer risk reduction was reported particularly in women, some authors showed no improvement or even increased cancer incidence. Although various studies have reported beneficial effects of surgery on risk of specific cancer development, fundamental insights into the pathogenesis of obesity-related cancer are indispensable to fully elucidate its mechanisms.